Mixed methods evaluation of vaping and tobacco product use prevention interventions among youth in the Florida 4-H program. (June 2023) - Bteddini, Dima S.; LeLaurin, Jennifer H.; Chi, Xiaofei; Hall, Jaclyn M.; Theis, Ryan P.; Gurka, Matthew J.; Lee, Ji-Hyun; Mobley, Erin M.; Khalil, George E.; Polansky, Caroline J.; Kellner, Allie M.; Fahnlander, Alexandra M.; et al.
Highlights: This study used mixed-methods to evaluate the feasibility of two vaping prevention programs. A randomized controlled trial design was implemented. Both programs had positive effects on tobacco prevention outcomes. Abstract: Introduction: Novel prevention programs are developed to address the increase in e-cigarette use (vaping) among children. However, it remains paramount to test their feasibility in rural settings. This pilot study implemented and evaluated the feasibility and outcomes of two innovative programs, CATCH My Breath and smokeSCREEN, among youth in rural settings in Florida. Methods: We conducted four focus groups with youth aged 11–17 recruited from 4-H rural clubs in Florida. In a subsequent randomized trial, we recruited 82 youth participants and assigned them to one of three arms: CATCH My Breath, smokeSCREEN, or control. CATCH My Breath and smokeSCREEN participants attended online group intervention sessions while the control group received educational material. Pre- and post-surveys were administered to all participants to assess knowledge, susceptibility, perceived positive outcomes and risk perceptions related to tobacco and e-cigarette use. Other feasibility parameters were also assessed. Results: Focus group discussions provided insights about feasibility and informed the implementation of both interventions in terms of delivery format, scheduling of sessions and incentives. After the intervention, CATCH My Breath participants significantly improved their general tobacco-related knowledge (post-pre = 16.21–12.92 = 3.3, p <.01) and risk perceptions towards other flavored tobacco products (post-pre = 19.29–17.71 = 1.6, p <.05). smokeSCREEN participants significantly improved their general tobacco knowledge (post-pre = 18.77–13.77 = 5.0, p <.01), knowledge about e-cigarettes (post-pre = 9.08–6.31 = 2.8, p <.01) and risk perception towards e-cigarettes (post-pre = 24.69–21.92 = 2.8, p <.05). Conclusions: This study demonstrated feasibility of delivering the interventions via participant engagement, participants' willingness to be randomized, assessment of outcome measures, and exploration of different recruitment methods. Despite the potential positive influence of CATCH My Breath and smokeSCREEN on youth participants, further evaluation with larger samples is needed.